Future healthcare professionals on working conditions in Poland: perspective of medical university students - Izabela Rydlewska-Liszkowska; Agnieszka Strzelecka; Anna Rybarczyk-Szwajkowska (Nofer Institute of Occupational Medicine, 2024)
Background Students of medical universities, future employees, will have an impact on the shaping healthcare system. It is important to know and understand their opinions on the factors affecting working conditions and, consequently, changes necessary to improve effectiveness of health care. Students' expectations can contribute to the changing working conditions for graduates and bring added value to health system redefinition. Material and Methods The study used factor analysis to check whether its use was justified. Reliability analysis was performed and structure indicators were determined for each question. The anonymous survey was conducted from September 2017 until March 2018; 1205 students were randomly selected for the sample. Results Eighty percent of the students declared interest in healthcare changes, >50% reported that the main factors influencing the work were competencies, financing, medical equipment and organization. Over 90% of the respondents indicated too long wait times for an appointment with a specialist and admission to hospital as the reason for the low efficiency of healthcare, whereas >80% of the survey participants considered insufficient funding to be a barrier. The need for changing the financing scheme was underlined by >90% of the students, and of health priorities by about 80%. Approximately 71% of the respondents were in favour of limiting the role of government in decision-making processes and introducing changes into the education system. Conclusions Students' views on organizational and financial factors of working conditions can contribute to improvement in systemic solutions at both micro and macro levels. Limiting the role of politicians in planning and implementing reforms can motivate employees to be more creative and decisive. Analysis of opinions can bring added value to health policy and systemic changes and should be extended by further research results after the COVID-19 pandemic. Students' interest in healthcare reform encourages reflection on enriching education with managerial skills. Med Pr Work Health Saf. 2024;75(4):321-332